Emerging vectors of narratology - Hansen, Per Krogh; Pier, John; Roussin, Philippe; Schmid, Wolf (Narratologia, 2017)
Narratology has been flourishing in recent years thanks to investigations into a broad spectrum of narratives, at the same time diversifying its theoretical and disciplinary scope as it has sought to specify the status of narrative within both society and scientific research. The diverse endeavors engendered by this situation have brought narrative to the forefront of the social and human sciences and have generated new synergies in the research environment. Emerging Vectors of Narratology brings together 27 state-of-the-art contributions by an international panel of authors that provide insight into the wealth of new developments in the field. The book consists of two sections. "Contexts" includes articles that reframe and refine such topics as the implied author, narrative causation and transmedial forms of narrative; it also investigates various historical and cultural aspects of narrative from the narratological perspective. "Openings" expands on these and other questions by addressing the narrative turn, cognitive issues, narrative complexity and metatheoretical matters. The book is intended for narratologists as well as for readers in the social and human sciences for whom narrative has become a crucial matrix of inquiry